Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations MAIN RATES OF WEEKLY CONTRIBUTIONS CLASS I (EMPLOYED PERSONS) MEN WOMEN Age Paid by Employee Paid by Employer Total Paid by Employee Paid by Employer Total 18 and over 4s. 11d. 4s. 2d. 9s. 1d. 3s. 10d. 3s. 3d. 7s. 1d. Under 18 2s. 10 1/2 d 2s. 5 1/2 d. 5s. 4d. 2s. 4d. 1s. 11d. 4s. 3d. CLASS 2 (SELF-EMPLOYED PERSONS) MEN WOMEN 18 and over 6s. 2d. 18 and over 5s. 1d. Under 18 3s.7d. Under 18 3s. 1d. CLASS 3 (NON-EMPLOYED PERSONS) MEN WOMEN 18 and over 4s. 8d. 18 and over 3s. 8d. Under 18 2s. 9d. Under 18 2s. 3d. 6. How are Contributions paid? Contributions are paid by National Insurance stamps — on a single contribution card — to the value of the total contribution. These stamps can be bought only at a Post Office. Your new National Insurance contribution card will be supplied either to you or to your employer. If it has not been 7 345/3/2/10